Back Cover: Recyclable Mitsunobu Reagents: Catalytic Mitsunobu Reactions with an Iron Catalyst and Atmospheric Oxygen (Angew. Chem. Int. Ed. 17/2013). Issue 17 (8th April 2013) - Hirose, Daisuke; Taniguchi, Tsuyoshi; Ishibashi, Hiroyuki
<x xml:space="preserve">Abstract</x> Ethyl 2‐arylhydrazinecarboxylates, which are aerobically oxidized by iron catalysis into the corresponding azo species, can act as recyclable reagents in the Mitsunobu reaction. In their Communication on page 4613 ff., Taniguchi et al. report Mitsunobu reactions using catalytic amounts of these hydrazine reagents and iron phthalocyanine in the presence of air.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>